Fungsi Pengawasan Dinas Perhubungan dalam Penertiban Tarif Angkutan di Provinsi Bali - Komang Ikka Shintya Daivi; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Warmadewa Press, 2022)
Public transportation is one part of the transportation sector that is widely used by the Balinese people. An important component in the operation of public transportation that must be considered is the determination of tariffs. The purpose of the study was to analyze the mechanism for controlling public transport fares by the Bali Provincial Transportation Service and to examine the obstacles during the implementation of controlling public transport fares in the Province of Bali. The research method in this paper uses empirical research using a sociological approach and a conceptual approach. The results show that the Government has limited authority in setting tariffs. The authority for public transportation rates for people in Bali Province includes online transportation, conventional taxis, and AKDP transportation. As a result of the pandemic, most entrepreneurs in the transportation sector have lost, this is a factor in the existence of fraud in the imposition of tariffs. In addition, the lack of PPNS personnel and the unavailability of special tools to read barcodes are also obstacles. The Department of Transportation is advised to review comprehensive tariff rules, as well as add PPNS members, and immediately budget for the availability of sophisticated equipment in order to overcome the obstacles that occur.